The effect of polytetrafluoroethylene particle size on the properties of biodegradable poly(butylene succinate)-based composites - Shudong Chen (Nature Portfolio, 2021)
Abstract Poly(butylene succinate) (PBS)/polytetrafluoroethylene (PTFE) composites, including three types of PTFE powders, were prepared by melt blending using a HAAKE torque rheometer. Microcellular foams were successfully fabricated by batch foaming with supercritical fluids (scCO2). The effects of PTFE powder type on crystallization, rheological properties and foaming behavior were studied. PTFE L-5 and PTFE JH-220 powders showed good dispersion in the PBS matrix, and PTFE FA-500 powder underwent fibrillation during the melt blending process. All three PTFE powders gradually increased the crystallization temperature of PBS from 78.2 to 91.8 ℃ and the crystallinity from 45.6 to 61.7% without apparent changes in the crystal structure. Rheological results revealed that PBS/PTFE composites had a higher storage modulus, loss modulus, and complex viscosity than those of pure PBS. In particular, the complex viscosity of the PBS/P500 composite increased by an order of magnitude in the low-frequency region. The foamed structure of PBS was obviously improved by adding PTFE powder, and the effect of fibrillated PTFE FA-500 was the most remarkable, with a pore mean diameter of 5.46 μm and a pore density of 1.86 × 109 cells/cm3 (neat PBS foam: 32.49 μm and 1.95 × 107 cells/cm3). Moreover, PBS/P500 foam always guarantees hydrophobicity.